X-pinch source of subnanosecond soft X-ray pulses based on small-sized low-inductance current generator; Journal of Experimental and Theoretical Physics Letters (JETP Letters); Vol. 111, iss. 3 - Mesyats G. A. Gennady Andreyevich; Shelkovenko T. A.; Ivanenkov G. V.; Agafonov G. V.; Savinov S. Yu.; Pikuz S. A.; Tilikin I. N.; Tkachenko S. I.; Chaikovskii S. A.; Ratakhin N. A. Nikolay Aleksandrovich; Fedushchak V. F.; Oreshkin V. I. Vladimir Ivanovich; et al. (2010, 2010)
Title screen